Cheese from Non-Bovine Milk - Papademas, Photis; Bintsis, Thomas (My University, 2022)
Non-bovine milk cheeses, although mainly produced in the Mediterranean basin, are widely accepted and enjoyed worldwide. This chapter discusses the importance of non-bovine milk cheeses for local economies, cultural heritage and the role in preserving biodiversity. The special characteristics, composition, as well important parameters, such as animal feeding regimes/farming systems, and cheese-making technologies are presented. The diversity is clearly reflected in the organoleptic profile of every cheese in the relevant category i.e., soft, semi-hard, hard, mold surface-ripened, blue pasta-filata, blue-veined, whey or white-brined, making non-bovine milk cheeses unique.
Keywords: Ovine; Caprine; Buffalo; Non-bovine; Cheese; Cheese categories; Maturation; Feeding regimes; Farming systems